In Vitro Comparative Evaluation of Newly Produced Desensitizer, Chlorhexidine and Gluma on Bond Strength and Bond Longevity of Composite to Dentin - Reza Davalloo; Seyedeh Maryam Tavangar; Heshmatollah Ebrahimi; Farideh Darabi; Shima Mahmoudi (Shiraz University of Medical Sciences, 2020)
Statement of the Problem: Etching process on dentin can activate matrix metalloproteinase (MMP) which hydrolyze organic matrix of demineralized dentin. Gluma and chlorhexidine could inhibit the activation of MMP. Purpose: The aim of the study was to evaluate the effect of a new desensitizing material consisting of Gluma and chlorhexidine together on the shear bond strength and bond durability of composite restorations. Materials and Method: One hundred and twenty caries-free extracted premolars were sectioned horizontally from one third of the coronal crown to expose flat dentin surface and randomly divided into 4 groups. In the control group, no surface treatment was used. In the first group chlorhexidine (CHX) 2%, in the second group, new material (NM) and in third group Gluma desensitizer (GD) was applied after etching and before bonding(total-etch bonding system). After the bonding process, the composite was placed on the surface of the samples using a cylindrical mold. Then, the shear bond strengths of half of the specimens were measured after 24 hours and the other half after 6 months of storage in distilled water and thermocycling. The failure types of specimens were evaluated with a stereomicroscope. Data were analyzed using One-way Anova and Tukey's Post Hoc tests in SPSS software. Results: After 6 months, the bond strength decreased in all groups and differences were statistically significant (p= 0.002).The highest shear bond strength was observed after 6 months in the NM group and the GD group with no statistically significant difference. The 24-hour bond strengths were not significant between groups. Mix failure had the highest rate in all groups. Conclusion: It can be concluded that the effect of combination of chlorhexidine and Gluma on maintaining the integrity and strength of bond over time is similar to Gluma compound alone and they have better effect than chlorhexidine.